Kritik Konsumerisme Budaya Musik dalam Tren Lagu Mas Dho: Analisis Teori Kritis Mazhab Frankfurt dan Perspektif Islam - Karimah, Naila Niswatul; Muna, Arina Sabilal; Saidah, Saidah; Zahid, A. (Canonia Religia, 2025)
This study examines the phenomenon of industrial culture reflected in the trend of Javanese koplo dangdut music popularized by Mas Dho among Indonesian millennials. Using a descriptive qualitative approach, data were gathered through interviews with Mas Dho’s listeners and content analysis of social media platforms. Guided by the Critical Theory of the Frankfurt School and Islamic ethical perspectives, the findings reveal that the popularity of Mas Dho’s songs exemplifies cultural commodification, where music is transformed into a market-driven product within the capitalist system. This commodification fosters a false consciousness among consumers, subtly aligning their cultural tastes with industrial interests. From an Islamic viewpoint, music consumption is not merely an aesthetic act but a moral engagement that demands adherence to spiritual and ethical values. The research emphasizes critical awareness in consuming popular culture and calls for balancing artistic freedom with Islamic principles of morality, modesty, and social responsibility. In this light, the study invites a rethinking of how cultural products should foster moral consciousness rather than serve solely as instruments of capitalist commodification.